Somatic symptom disorder was common in children and adolescents attending an emergency department complaining of pain. - Cozzi, Giorgio; Minute, Marta; Skabar, Aldo; Pirrone, Angela; Jaber, Mohamad; Neri, Elena; Montico, Marcella; Ventura, Alessandro; Barbi, Egidio (Acta Paediatr, 2017)
AIM: The aim of this study was to quantify the prevalence of somatic pain in a paediatric emergency department (ED). METHODS: We conducted a prospective observational study using patients admitted to the ED of an Italian children's hospital between December 2014 and February 2015. We enrolled children aged 7-17 who turned up at the ED complaining of pain. Patients and parents were asked to fill in a questionnaire to allow the analysis of the patients' medical history and provide contact details for follow-up. We divided the enrolled patients into four groups: post-traumatic pain, organic pain, functional pain and somatic pain. The questionnaire was used to define pain characteristics and to generate an impairment score. RESULTS: Of the 713 patients who met inclusion criteria, 306 (42.9%) were enrolled in the study. Of these, 135 (44.0%) suffered from post-traumatic pain, 104 (34.0%) from organic pain, 41 (13.4%) from functional pain and 26 (8.6%) from somatic pain. Somatic pain patients had endured pain longer, had missed more school days and had suffered severe functional impairment. CONCLUSION: This study highlighted that somatic pain was a significant contributor to paediatric emergency room visits and should be suspected and diagnosed in children reporting pain.
Keywords: Adolescent; Child; Emergency Service, Hospital; Female; Humans; Italy; Male; Medically Unexplained Symptoms; Pain; Prospective Studies

A Spotted Bone. - Perin, Silvia; Rabach, Ingrid; Pascolo, Paola; Dibello, Daniela; Ventura, Alessandro (J Pediatr, 2016)

A Shining Scrotal Fountain. - Copertino, Marco; Benelli, Elisa; Gregori, Massimo; Barbi, Egidio; Ventura, Alessandro (J Pediatr, 2015)
Keywords: Child; Edema; Humans; Male; Penile Diseases; Scrotum

Sirolimus Therapy in Congenital Hyperinsulinism: A Successful Experience Beyond Infancy. - Minute, Marta; Patti, Giuseppa; Tornese, Gianluca; Faleschini, Elena; Zuiani, Chiara; Ventura, Alessandro (Pediatrics, 2015)
Congenital hyperinsulinism (CHI) due to diffuse involvement of the pancreas is a challenging and severe illness in children. Its treatment is based on chronic therapy with diazoxide and/or octreotide, followed by partial pancreatectomy, which is often not resolutive. Sirolimus, a mammalian target of rapamycin inhibitor, was reported to be effective in treating CHI in infants. We report here the case of an 8-year-old boy affected by a severe form of CHI due to a biallelic heterozygous ABCC8 mutation who responded to sirolimus with a dramatic improvement in his glucose blood level regulation and quality of life, with no serious adverse events after 6 months of follow-up. To the best of our knowledge, this is the first report of a successful intervention in an older child. It provides a promising basis for further studies comparing sirolimus with other treatments, particularly in older children.

Splenic Infarction in Acute Infectious Mononucleosis. - Naviglio, Samuele; Abate, Maria Valentina; Chinello, Matteo; Ventura, Alessandro (J Emerg Med, 2015)
BACKGROUND: The evaluation of a febrile patient with acute abdominal pain represents a frequent yet possibly challenging situation in the emergency department (ED). Splenic infarction is an uncommon complication of infectious mononucleosis, and may have a wide range of clinical presentations, from dramatic to more subtle. Its pathogenesis is still incompletely understood, yet it may be associated with the occurrence of transient prothrombotic factors. CASE REPORT: We report the case of a 14-year-old boy who presented with fever, sore throat, left upper quadrant abdominal pain, and splenomegaly, with no history of recent trauma. Laboratory tests revealed a markedly prolonged activated partial thromboplastin time and positive lupus anticoagulant. Abdominal ultrasonography showed several hypoechoic areas in the spleen consistent with multiple infarctions. Magnetic resonance imaging eventually confirmed the diagnosis. He was admitted for observation and supportive treatment, and was discharged in good condition after 7 days. WHY SHOULD AN EMERGENCY PHYSICIAN BE AWARE OF THIS?: Spontaneous splenic infarction should be considered in the differential list of patients presenting with left upper quadrant abdominal pain and features of infectious mononucleosis; the diagnosis, however, may not be straightforward, as clinical presentation may also be subtle, and abdominal ultrasonography, which is often used as a first-line imaging modality in pediatric EDs, has low sensitivity in this scenario and may easily miss it. Furthermore, although treatment is mainly supportive, close observation for possible complications is necessary.

Subcutaneous panniculitis-like T-cell lymphoma presenting with diffuse cutaneous edema in a 2-year-old child. - Chinello, Matteo; Naviglio, Samuele; Remotti, Daniele; Locasciulli, Anna; Ventura, Alessandro (J Pediatr Hematol Oncol, 2015)
Keywords: Child, Preschool; Edema; Humans; Lymphoma, T-Cell; Male; Panniculitis; Skin Diseases

Severe inflammatory bowel disease associated with congenital alteration of transforming growth factor beta signaling. - Naviglio, Samuele; Arrigo, Serena; Martelossi, Stefano; Villanacci, Vincenzo; Tommasini, Alberto; Loganes, Claudia; Fabretto, Antonella; Vignola, Silvia; Lonardi, Silvia; Ventura, Alessandro (J Crohns Colitis, 2014)
Transforming growth factor beta is a pleiotropic cytokine which plays a central role in the homeostasis of the immune system. A complex dysregulation of its signaling occurs in Loeys-Dietz syndrome, a monogenic disorder caused by mutations of transforming growth factor beta receptors type 1 or type 2, characterized by skeletal involvement, craniofacial abnormalities, and arterial tortuosity with a strong predisposition for aneurysm and dissection. In addition, several immunologic abnormalities have been described in these patients, including an increased risk of allergic disorders as well as eosinophilic gastrointestinal disorders. The occurrence of inflammatory bowel disorders has been also reported, but it is poorly documented. We describe two unrelated children with Loeys-Dietz syndrome affected by severe chronic inflammatory colitis appearing at an early age. The intestinal disease presented similar features in both patients, including a histopathological picture of non-eosinophilic chronic ulcerative colitis, striking elevation of inflammatory markers, and a distinctly severe clinical course leading to failure to thrive, with resistance to multiple immunosuppressive treatments. One of the patients also presented autoimmune thyroiditis. Our report confirms that chronic ulcerative colitis may be associated with Loeys-Dietz syndrome. This finding suggests that an alteration of transforming growth factor beta signaling may by itself predispose to inflammatory colitis in humans, and represent an invaluable model to understand inflammatory bowel diseases.
Keywords: Child, Preschool; Colon; Colonoscopy; Female; Humans; Infant; Inflammatory Bowel Diseases; Loeys-Dietz Syndrome; Male; Signal Transduction; Transforming Growth Factor beta

Should cardiac involvement be included in the criteria for diagnosis of Churg Strauss syndrome? - Amaddeo, Alessandro; Ventura, Alessandro; Marchetti, Federico; Benettoni, Alessandra; Londero, Margherita (J Pediatr, 2012)
Keywords: Adolescent; Churg-Strauss Syndrome; Heart Diseases; Humans; Male

Slow growth: do not forget the thyroid. - Tornese, Gianluca; Tonini, Giorgio; Ventura, Alessandro (J Pediatr Gastroenterol Nutr, 2012)
Keywords: Constipation; Female; Humans; Hypothyroidism; Male; Thyroid Function Tests

Successful induction of oral tolerance in Netherton syndrome. - Pastore, Serena; Gorlato, Gaia; Berti, Irene; Barbi, Egidio; Ventura, Alessandro (Allergol Immunopathol (Madr), 2012)
Keywords: Allergens; Alopecia; Child, Preschool; Desensitization, Immunologic; Disease-Free Survival; Eczema; Female; Food Hypersensitivity; Hair Follicle; Humans; Immune Tolerance; Immunoglobulin E; Infant, Newborn; Mouth; Netherton Syndrome; Treatment Outcome

Safety and efficacy of high-dose acarbose treatment for dumping syndrome. - De Cunto, Angela; Barbi, Egidio; Minen, Federico; Ventura, Alessandro (J Pediatr Gastroenterol Nutr, 2011)
Dumping syndrome (DS) is a complication of Nissen fundoplication. Dietary strategies can ameliorate symptoms, but this approach is not always foolproof. Limited evidence reports the efficacy of acarbose for children who are unresponsive to feeding manipulations. We report 8 patients with DS aged between 7 and 24 months. In 4 of 8 nutritional strategies failed, and acarbose treatment was started. The initial dose was 25 mg for meals, and increased until postprandial glucose was stable. In 3 of 4 children the final dose was higher than previously reported, without adverse effects. Acarbose is useful to treat DS in cases of failure of dietary strategies.
Keywords: Acarbose; Child, Preschool; Dumping Syndrome; Female; Humans; Hyperglycemia; Hypoglycemic Agents; Infant; Male; Postprandial Period; Treatment Outcome